A Review of Ethanobotanical and Phytopharmacology ofOtteliaalismoides (L.)PERS (International Journal of Research in Pharmacology & Pharmacotherapeutics, 2021)
The use of natural products as medicinal plants presumably predates the earliest recorded history. In the past 20 years public dissatisfaction with the cost prescription medications, combined with an interest in returning to natural or organic remedies, has led to an increase in herbal medicine use. Herbal medicine also called botanical medicine or phytomedicine refers to using a plant's seeds, berries, roots, leaves, barks and flowers for medicinal purposes. Otteliaalismoides is an traditional aquatic plant. The plant well below the surface of water usually anchored. Found both in stagnant and running water. It is used as medicinal plant for treating diseases like cancer, asthma, diabetes, tuberculosis, haemorrhoids, febrifuge, and rubifacient. Our present aim is to review all the work performed on the plant to get the clear idea to evaluate its various medicinal principles relating to ethanobotanical and phytopharmacological approaches.